The Effect of Stevia Consumption on Glycemic Control in Elderly Patients with Diabetes: A Literature Review - Alhalawi, Zikri; Ervita, Ledy (Journal of Community Development and Disaster Management, 2025)
Diabetes mellitus (DM) represents a significant health challenge among elderly populations, characterized by chronic hyperglycemia requiring strict dietary management. Stevia rebaudiana Bertoni, a natural low-calorie sweetener, has emerged as a promising therapeutic adjunct for diabetes management. This study aimed to evaluate the effects of stevia consumption on glycemic control in elderly patients with diabetes mellitus through comprehensive literature synthesis. A literature review was conducted across multiple scientific databases (Emerald Insight, ProQuest, PubMed, ScienceDirect, EBSCO, and Google Scholar) covering publications from 2015-2025. Initial screening of 312 articles yielded 6 studies meeting inclusion criteria, focusing specifically on stevia utilization as a sugar substitute for elderly diabetic patients. Analysis revealed that stevia demonstrates superior glycemic control properties compared to conventional sweeteners, with sweetness intensity 100-300 times greater than sucrose while maintaining zero caloric content. Stevia represents an effective and safe natural sweetener alternative for elderly patients with diabetes mellitus. Its hypoglycemic properties, antioxidant effects, and absence of adverse effects position it as a valuable therapeutic tool for diabetes management. The findings support stevia's potential development as a nutraceutical supplement and its integration into dietary recommendations for elderly diabetic populations, contributing to improved quality of life and enhanced glycemic control.